ANALISIS KEAMANAN SISTEM INFORMASI AKADEMIK UIN SUNAN KALIJAGA - Aries Firmansyah; Bambang Sugiantoro (Jurusan Teknik Informatika, 2017)
The Academic Information System is is designed to support what you want users completed, the operating system must support the network to a certain extent. Therefore the need to be analysed performance computer network on information systems academic UIN Sunan Kalijaga Yogyakarta later the analysis can be used for development in the future. Testing tissue using a performance QoS (Quality of Service) and testing attacks have DDOS.Research phase based on the quantitative method as the data collection to knowing how big performance of the academic information system to DDOS attack, scenario using big packet sent and conducted performance analysis of performance of the Academic Information System of UIN Sunan Kalijaga Yogyakarta emphasizes on monitoring of system and bandwidth parameters measurement, delay and packet loss on the network infrastructure that has been there is.The result of measurement and monitoring Quality of Service on Academic Information System of UIN Sunan Kalijaga toward the Distributed Denial of Service attack (DDoS) decreased by the highest average score of bandwidth transfer rate 2.4 KBps what happened in the 1 PC attack and 10.1 KBps what happened in 2 PC attack. According to THIPON version, delay parameters indicated the average score of delay is bigger than 450 ms what happened in 1 PC attack by score 928.3 ms and 2 PC score 880.6 ms included in bad category. Meanwhile on packet loss parameters of 1 PC attack score 50.5 % and 2 PC score 82.2 % included in bad category that is by packet loss ranges more than 25 %.